Changes in Cardiovascular Health and Functional Fitness Following Multicomponent Exercise Training in Community-Dwelling Older Women - Sandra Silva-Santos; Paula Rodrigues; Cidália Freitas; Joana Pinto; Raphael José Perrier-Melo; Manoel J. Rios (Physiologia, 2026)
Background: Multicomponent exercise promotes healthy aging, but evidence in community-dwelling older women remains limited. This study examined pre–post changes in functional fitness and cardiovascular health following participation in a six-month multicomponent exercise program. Methods: Thirty-five community-dwelling older women (71.39 ± 6.82 years) participated in a quasi-experimental pre–post intervention study. Participants completed supervised multicomponent exercise sessions twice weekly for six months. Anthropometric, cardiovascular, and functional fitness outcomes were assessed before and after the program. Results: Reductions were observed in body mass (68.03 ± 11.39 vs. 66.29 ± 10.02 kg; p < 0.001) and body mass index (26.56 ± 3.71 vs. 25.90 ± 3.22 kg·m−2; p < 0.05). Lower post-test values were also observed for systolic blood pressure (125 ± 9 vs. 121 ± 10 mmHg; p = 0.026), resting heart rate (85 ± 12 vs. 77 ± 11 bpm; p = 0.008), and double product (10,359 ± 1899 vs. 9701 ± 1705 mmHg·bpm; p = 0.027). Handgrip strength was higher at post-test in both the dominant hand (20.98 ± 5.47 vs. 22.53 ± 6.31 kgf; p = 0.007) and non-dominant hand (19.23 ± 4.99 vs. 21.20 ± 5.61 kgf; p < 0.001). Functional aerobic capacity was also higher at post-test (95.74 ± 21.35 vs. 110.41 ± 22.86 steps; p < 0.001), while flexibility values were higher in the left Chair Sit-and-Reach Test (−15.92 ± 10.48 vs. −12.97 ± 10.91 cm; p = 0.001) and left Back Scratch Test (−3.65 ± 6.82 vs. 4.32 ± 7.83 cm; p < 0.001). Conclusions: Participation in a twice-weekly multicomponent exercise program for six months was associated with favorable pre–post changes in functional fitness and cardiovascular health in community-dwelling older women.